LITERATURE STUDY: LEARNING MEDIA TO IMPROVE THE UNDERSTANDING OF HIGH SCHOOL STUDENTS ON ELEMENTAL CHEMISTRY - Alfiyah Darojat; Riza Faishol (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This research aims to identify and select appropriate learning media that align with the characteristics of Chemical Elements material. In the introduction, it is explained that learning occurs through the interaction between individuals and their environment. However, many students are not interested in learning Chemical Elements due to the lack of attractiveness from the used instructional media. Therefore, this research has novelty in finding suitable learning media for studying Chemical Elements. The research method used is literature review with descriptive analysis. Literature search was conducted using sources such as Google Scholar, Garuda, and ResearchGate. The data were analyzed using content analysis. The results of the study indicate several types of learning media that are suitable for use in teaching Chemical Elements material. First, virtual laboratories can provide practical experience through simulation for students so they can think critically and logically without having to conduct direct experiments in a real laboratory setting. Second, interactive multimedia provides stimulus for learning by utilizing sensory functions and facilitates student understanding of the material. Third, bulletins are printed media that have been validated by experts and received positive responses from students as aids in learning Chemical Elements subject matter. Fourth, word guessing games can significantly improve content validity as well as student's learning outcomes in Chemistry Unsur material effectively.In addition,it is also mentioned that box-word game media and element adventure games can be used during the process of studying Chemical elements.The two types of media have been validated by validatorsand received positive responses from students.These various medias provide an interactive learning experience,enrich student understanding,and receive positive feedback from them.This research provides important information regarding various appropriate instructional media aligned with the characteristics of Chemistry Unsur to enhance student understanding towards these materials.